Epidemiological and genetic analysis concerning the non‐enterovirus 71 and non‐coxsackievirus A16 causative agents related to hand, foot and mouth disease in Anyang city, Henan Province, China, from 2011 to 2015. Issue 10 (29th May 2017) - Li, Yang; Bao, Honghong; Zhang, Xiangping; Zhai, Mingqiang; Bao, Xiaobing; Wang, Demin; Zhang, Shuanhu
Abstract : Enterovirus 71 (EV‐A71) and coxsackievirus A16 (CV‐A16) are major pathogens of hand, foot, and mouth disease (HFMD) and have been associated with consecutive outbreaks of HFMD in China over the past years. Although several other human enteroviruses (HEVs) have also acted as causative agents of HFMD, published information on their roles in the prevalence of HFMD is limited. This study was conducted to reveal the characteristics of the pathogenic spectrum and molecular epidemiology of the non‐EV‐71 and ‐CV‐A16 HEVs in Anyang City, which is located in north‐central China and has a population of five million. From 2011 to 2015, 2270 samples were collected from HFMD patients (3.89 ± 1.06 years of age), and 1863 HEV‐positive samples, including 524 samples with 23 non‐EV‐71 and non‐CV‐A16 serotypes, were identified. Based on the nucleotide sequence of the VP1 gene, 6 common non‐EV‐71 and non‐CV‐A16 HEVs, including coxsackievirus A2, A6, A10, A14, B2, and B5, were studied to determine their phylogenies and selective pressures. Phylogenetic analyses revealed a high level of genetic divergence and a pattern of lineage replacement over time in Mainland China. Selective pressure analyses showed that purifying selection was predominant in the evolution of the VP1 gene, whereas positive selection acted on individual codons. Overall, non‐EV‐71 and non‐CV‐A16 HEVs were important constituents of the pathogenic spectrum of HFMD in Anyang City during 2011‐2015. Some of these HEVs with complex and active phylogenies represent a potential threat to public health, suggesting that long‐term monitoring of these pathogens should be implemented to prevent HFMD outbreaks.